THE IMPLEMENTATION OF INTERACTIVE LEARNING MEDIA USING MACROMEDIA FLASH FOR PRIMARY EDUCATION IN TARAKAN - Vega, Nofvia De; Rafiqa, Syarifa (Universitas Borneo Tarakan, 2019)
The objectives of this research are to describe the implementation of interactive learning media using macromedia flash and to describe the teachers’ and students’ responds of this interactive learning media using macromedia flash for primary education in Tarakan. The instrument of this research was the researcher herself. The approach used in this study is essentially qualitative with complementary quantitative data. The qualitative research used to see the procedure of the real fact implementing of interactive learning media using macromedia flash for primary education in Tarakan. The supportive quantitative analysis was employ to measure the highest score of teachers’ and students’ responses in the questionnaire. The data were analyzed by using non-parametric statistics. Meanwhile, qualitative analysis is used to describe the data in words or in making interpretations on the findings based on interview by the teacher and classroom observation checklist. The result showed that media was appropriate to make students’ interest in learning English, the media and topics were also related to syllabus such as numbers, alphabet, colors, things, and parts of body. Based on teachers’ responses of questionnaire, there are 5 (100%) teachers respectively confirmed option A that they assumed that media is very important and can help them in teaching and learning process especially in English subject. Meanwhile, based on students’ responses of questionnaire showed that the highest percentage was 21 (72,44%) students respectively confirmed option A that media can be helped in understanding English language.